Identification of Characteristics and Distribution of Subsurface Coal Using the 2D Geoelectric Method in Tanjung Palas Timur District, North Kalimantan - Putri Sekar Ayuningsih; Sutrisno Dipl.Seis; Tati Zera; Nur Hidayat S.T, M,Si (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
Based on regional geology, Tanjung Palas Timur Subdistrict is included in the only formation, which includes coal seams. The depletion of oil and gas energy sources in Indonesia results in the need for other alternative energy sources, one of which is coal. This study aims to determine the characteristics of coal in the study area. This research was conducted in Tanjung Palas Timur Subdistrict, North Kalimantan using the geoelectric resistivity method with a pole-pole configuration and 8 tracks which are divided into 2 track blocks. The resistivity geoelectric method is used because it is very suitable for mining exploration. Data processing was done in 2D using Res2dinv software and 3D using Rockworks15 software. The results of the geoelectric data processing of line 1 to 8 show that the coal seam in the study area has a resistivity of 10-30 Ωm with a thickness varying from 17.22 m - 60 m as a type of lignite coal. In addition, the research area is also dominated by layers of clay and sandstones. The continuity of the coal seam is also seen in block 1 from line 3 in the southwest direction to line 1 in the northeast direction.